Pengembangan Perangkat Pembelajaran Matematika Model Learning Cycle 7e Siswa Kelas X SMA Pada Tahap Validitas - Sri Ulfa Insani (Departement of Mathematics Education, 2020)
The aim of this research is to produce trigonometry instructional package with learning cycle 7e model based on the aspect of validity, practicality, and effectiveness in terms of problem solving skill and curiosity of 10th grade senior High School students. There are seven phases of learning cycle 7e model consisting of elicit, engage, explore, explain, elaborate, evaluate, and extend. The developed instructional package consists of lesson plans and worksheets. This study was research and development. The developing model in this research used ADDIE’s model (Analyze, Design, Develop, Implement, and Evaluate). The research instruments were validation sheets, teacher assessment quistionnaire, student assessment quistionnaire, observation sheets for learning implementation, problem solving skill tests, and curiosity questionnaire. The instructional package is effective if the percentage of students who meet the completion of a classical test on problem-solving skills tests reaches at least 75%, and if the percentage of questionnaire results students meet the high category with minimum 75%. The first step of this research is to carry out the analysis with the steps of conducting analysis of needed, analysis of material, and analysis of student character. In this step, lesson plans and worksheets were designed with learning cycle 7e model. To determine validity criteria, a validation sheet is used based on the expert's assessment. Then for the practicality used teacher assessment quistionnaire, student assessment quistionnaire, and observation sheets for learning implementation. Next to determine the effectiveness criteria seen from the results of student scores by giving problem solving skill tests, and curiosity questionnaire.